ANALISA KEBUTUHAN AIR IRIGASI SAWAH DESA MULYASARI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Jonizar, Jonizar; Revisdah, Revisdah; Royan, Noto; Al Fareza, Afifah Auliya (Universitas Muhammadiyah Palembang, 2024)
Water is one of the most essential needs for human existence; without it, life as we know it would not exist. While the Earth has a vast supply of water, only a small portion is usable. This study explores the relationship between water needs, availability, and irrigation efficiency specifically in rice field irrigation. To assess the amount of water required for irrigation, the KP-01 irrigation concept manual is utilized, while the F.J. Mock Method determines the amount of available water. Both figures are used to analyze the relationship between water needs and availability. In Mulyasari Village, the rice field irrigation system employs a rice-rice planting pattern across an area of 82 hectares. During the first planting season, the average water availability is 0.046 m³/sec, while the average water requirement is 0.073 m³/sec. In the second planting season, the average water availability decreases to 0.039 m³/sec, while the average water requirement increases to 0.096 m³/sec. The results indicate that in both planting seasons, the water needs have not been met based on the relationship between irrigation water availability and requirements. Additionally, there is one channel, tertiary channel III, that has not met the required standards. It operates at 70.09%, which is below the necessary threshold of 80% for tertiary channels.